EFFICACY OF AMNIOTIC MEMBRANE MESENCHYMAL STEM CELL THERAPY FOR BURN WOUNDS: META-ANALYSIS STUDY - Bermani, Bayu Fasi; Budi, Agus Santoso; Hutagalung, Magda Rosalina (Universitas Airlangga, 2020)
Highlights: The healing potential of stem cell therapy for burn wounds, primarily attributed to angiogenesis and anti-inflammatory effects. AM-MSC therapy has a beneficial impact on burn wound healing, particularly by promoting angiogenesis and reducing inflammation. Abstract: Introduction: Burn injury is a trauma with high morbidity and mortality that requires special management from the start. stem cells have generated great hopes for the treatment of numerous conditions including burns. The Metaanalysis was performed for these preclinical studies to assess the efficacy and possible mechanisms of Amniotic Membrane Mesenchymal Stem Cell (AM- MSC) in treating burn wounds. Methods: Seven studies identified by searching PubMed, MEDLINE, databases from inception to October 2020. In addition, a manual search of references of studies was performed to obtain potential studies. Stata 16 was used for all data analysis. Results: The overall meta-analysis showed that AM-MSC therapy significantly improved burn healing rate (SMD 3.34, 95% CI 1.82 to 4.86), irrespective of transplant type, burn area, and treatment method in the control group. Conclusions: Meta-analysis showed that AM-MSC therapy exerts appears to exert a positive effect in burn wound healing, mainly through angiogenesis and anti- inflammatory actions. There is, therefore, justification for continued efforts to evaluate variations in future clinical studies using stem cells to treat a burn wound in order to maximize the effectiveness. the use of stem cells as an adjunct to first- line therapies in burns.